2004
DOI: 10.1063/1.1777806
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the temperature of a premixed flame in a microcombustor

Abstract: We apply the scale analysis and the simulation to relate the flame temperature in a microcombustor to the external wall surface temperature. In deriving the equation for predicting the flame temperature, we account for the detailed reaction mechanisms in the combustion process and we assume that the flow in the combustor tube is laminar. Experimental investigations have been conducted to validate the equation. We employ hydrogen as a fuel and obtain a stable flame in microcombustors with internal radii of 3, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This explains qualitatively why the average temperature increases for the thin wall combustor. For a typical micro-combustor with a flame temperature of 1500 K [8], a 10% net reduction of axial heat loss predicts an increase of wall temperature for about 150 K, which is consistent with our experimental result. However, the thin wall structure is restricted by manufacturing and strength of material limits.…”
Section: Effect Of Wall Thickness To Combustor Diameter Ratiosupporting
confidence: 92%
See 1 more Smart Citation
“…This explains qualitatively why the average temperature increases for the thin wall combustor. For a typical micro-combustor with a flame temperature of 1500 K [8], a 10% net reduction of axial heat loss predicts an increase of wall temperature for about 150 K, which is consistent with our experimental result. However, the thin wall structure is restricted by manufacturing and strength of material limits.…”
Section: Effect Of Wall Thickness To Combustor Diameter Ratiosupporting
confidence: 92%
“…For TPV application, a micro-combustor with a backward facing step was developed by Yang et al [7], who showed that the backward facing step is capable of enhancing mixing process and prolonging residence time. Li et al [8] analyzed the combustion at micro-scale using scale analysis and numerical simulation to relate flame temperature explicitly to external wall temperature of the combustor. An excellent review on recent developments on the design of combustor for TPV system can be found in Colangelo et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the 1D flame model is a simplification as the scale analysis [10] noted that the reacting flow in the micro combustor is 2D in nature. However, the 1D assumption is well established and has been widely applied in studying laminar flame propagation [19][20][21]24,25]. Furthermore, Kaisare and Vlachos [37] compared the 1D and 2D (averaged in the radial direction) simulation results and noted that they were in reasonable quantitatively agreement.…”
Section: Resultsmentioning
confidence: 93%
“…Aside from these numerical studies, Leach et al [19] extended Mallard and Le Chatelier's (1D) thermal flame model to investigate the H 2 -air combustion in micro channels and noted that the heat exchange through the structure of the micro combustor leads to broadening of the reaction zone. Besides, Li et al applied the 1D flame model coupled with the heat conduction in the combustor wall and used it to correlate the flame temperature to the wall temperature [20] and analyze the entropy generation in the micro combustion process [21]. It should be noted that although Leach [20,21] to quantify two important ratios, namely, the heat loss ratio Q l /Q in (defined as the ratio of the heat loss from the flame to the heat generation in the reaction zone) and the heat recirculation ratio Q recir /Q l (defined as the ratio of the heat recirculation through the solid structure to the upstream to the heat loss from the flame).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation